1999
DOI: 10.1023/a:1020589829458
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Supernumerary embryos generated by IVF and ICSI should be frozen at the multicellular stage so as to allow selection of the best embryos for transfer and embryo freezing of only robust embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In practice, only a few studies about the superiority of blastocyst FET have been reported and each of them has presented different results. Some investigators have shown favorable pregnancy outcomes in blastocyst FET compared with other staged embryo FET [ 10 , 13 ]. Another study contradicted the former studies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, only a few studies about the superiority of blastocyst FET have been reported and each of them has presented different results. Some investigators have shown favorable pregnancy outcomes in blastocyst FET compared with other staged embryo FET [ 10 , 13 ]. Another study contradicted the former studies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%